Sleeping over - Denton, P. J.; Denos, Julia (New York : Aladdin Paperbacks, 2007)
Second graders Taylor, Emily, Jo, and Kara plan a sleepover party to celebrate the end of the school year, but Emily has to find a way to convince her parents that she is old enough to be away from home for the night.
4.9
3-6
3-6
Keywords: Sleepovers -- Fiction; Schools -- Fiction; Sleepovers -- Fiction; School stories